Rekonstruksi Konsep Bisnis Halalan Thayyiban Penguatan Integrasi-Interkoneksi Ekosistem Halal Value Chain - Bayumi, Muhamad Rahman; M. Iqbal,; Diem, M. Junestrada; Muhlis, (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2022)
The progress of the Halal Value Chain (HVC) ecosystem cannot be separated from the role of the government and other formal and informal institutions. In the HVC ecosystem, every organization/institution plays an important role in creating a halalan thayyiban business industry zone. One of the ways to promote halalization in supporting economic progress is to implement it through strengthening the Halal Value Chain in the economy. The purpose of this paper is to offer a reconstruction of the Halalan Thayiban business concept by strengthening the integration and interconnection of each subject in the HVC ecosystem. Using a descriptive qualitative approach, it is hoped that it will provide an overview of the concept of advancing a real HVC ecosystem. The results of this analysis will provide a long-term picture of the importance of promoting and accelerating HVC in terms of quality, not quantity. This study will discuss the reconstruction of the halalan thayyiban business concept and the importance of initiating an economic industry based on Islamic business ethics. By providing an overview and analysis of HVC acceleration efforts, it is hoped that this research will be oriented toward building the long term economy. Keywords: Reconstruction, Halalan Thayyiban, Integration and Interconnection, Islamic Business Ethics